RESEARCH OF SPECIFIC IMPACT OF OIL POLLUTION ON CHANGES IN PHYSIC-CHEMICAL PROPERTIES OF SOIL - Романович, І. С. (Scientific Progress & Innovations, 2014)
The basic physical and chemical properties of soil samples contaminated with crude oil are studied experimentally. The results of changes in physical and chemical characteristics of the soil as a result of oil pollution are presented; the influence of oil on the basic properties of the soil at different concentration levels of pollutant in the soil was analyzed. The conclusions regarding the impact of oil on the quality and water-soluble component of soil are made. The analysis of the determination of possible influence of oil pollution on groundwater was conducted.